2019
DOI: 10.1136/bjophthalmol-2019-313870
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety data for the XEN45 implant at 2 years: a retrospective analysis

Abstract: AimTo report efficacy and safety measures for XEN45 in a National Health Service setting after 24-month follow-up.MethodsThis is a retrospective, non-comparative audit of records of patients who underwent XEN45 procedure between June 2015 and May 2017. The main outcome measures were intraocular pressure (IOP) reduction and number of antihypertensive medications at each timepoint. Failure was defined as requiring further surgery or removal of XEN. Success was defined as 20% reduction of IOP without additional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
65
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 20 publications
16
65
5
1
Order By: Relevance
“…This greater need of needling can be explained by the absence of conjunctival dissection in the bleb site. In a retrospective study by Gabbay et al 19 , the needling rate after XEN implantation reported 37.7% which is similar to ours but in a 24 months follow-up period. Two elements could explain this.…”
Section: Discussionsupporting
confidence: 89%
“…This greater need of needling can be explained by the absence of conjunctival dissection in the bleb site. In a retrospective study by Gabbay et al 19 , the needling rate after XEN implantation reported 37.7% which is similar to ours but in a 24 months follow-up period. Two elements could explain this.…”
Section: Discussionsupporting
confidence: 89%
“…Rooney et al reported several cases of postoperative complications after XEN implantation. Gabbay et al also stated that patients should be advised regarding failure rates, possible need for bleb revision and the resumption of medication use after XEN implantation 16,48 .…”
Section: Discussionmentioning
confidence: 99%
“…13 . The IOP-lowering and medication-sparing efficacy of the XEN microstent has already been demonstrated in different single and multicenter trials 12,[14][15][16] . The aim of this study was to compare the efficacy and safety profile of the XEN microstent with standard TET in a comparable group of POAG cases in a retrospective, monocentric single surgeon setting.…”
mentioning
confidence: 91%
“…Three studies (Reitsamer, Gillmann and Gabbay) have reported 24-month results following Xen Gel Stent implanted ab interno without conjunctival dissection. [3][4][5] Overall, they reported comparable IOP reduction to mid-teens (14.2 ± 3.8 to 15.2 ± 4.2 mmHg) from mean baseline IOP ranging from 19.8 ± 8.2 mmHg to 22.1 ± 6.5 mmHg across these studies. Similarly, there was a comparable reduction in the mean IOP-lowering medication count, ranging from 2.0 ± 1.3 to 2.77 ± 1.1 at baseline, to 0.4 ± 0.7 to 1.0 ± 1.0 at 24 months.…”
Section: Introductionmentioning
confidence: 77%
“…During surgery, if the implant is immobile or excessively curled (ie, "pig tailed") or when interstitial resistance from intra-Tenon's placement is suspected, primary needling is recommended. 5 Currently, many surgeons are incorporating primary needling as part of their routine intraoperative procedure despite the concern that this step may be associated with an increased risk of subconjunctival bleeding, as ensuring supra-Tenon's placement may outweigh the risk of bleeding.…”
Section: Primary Needling (Intraoperative)mentioning
confidence: 99%